2017
DOI: 10.1038/s41598-017-02812-y
|View full text |Cite
|
Sign up to set email alerts
|

Insight into climate change from the carbon exchange of biocrusts utilizing non-rainfall water

Abstract: Biocrusts are model ecosystems of global change studies. However, light and non-rainfall water (NRW) were previously few considered. Different biocrust types further aggravated the inconsistence. So carbon-exchange of biocrusts (cyanobacteria crusts-AC1/AC2; cyanolichen crust-LC1; chlorolichen crust-LC2; moss crust-MC) utilizing NRW at various temperatures and light-intensities were determined under simulated and insitu mesocosm experiments. Carbon input of all biocrusts were negatively correlated with experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 77 publications
(153 reference statements)
0
18
0
2
Order By: Relevance
“…In addition, we had already observed that reductions in soil surface moisture negatively affect the C fixation rate of biocrust‐dominated areas during the first years of our experiment (Maestre et al ., ; Ladrón de Guevara et al ., ). We cannot rule out a possible direct effect of warming on lichen physiology because the increase of dark respiration with temperature is well documented in these organisms (e.g., Lange et al ., ; Lange & Green, ; Ouyang & Hu, ). Nevertheless, we do not think it was the main physiological impact as mosses had a positive response to warming, and increases in their respiration with warming can be similar to or even greater than that observed in lichens (Weber et al ., ; Ouyang & Hu, ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we had already observed that reductions in soil surface moisture negatively affect the C fixation rate of biocrust‐dominated areas during the first years of our experiment (Maestre et al ., ; Ladrón de Guevara et al ., ). We cannot rule out a possible direct effect of warming on lichen physiology because the increase of dark respiration with temperature is well documented in these organisms (e.g., Lange et al ., ; Lange & Green, ; Ouyang & Hu, ). Nevertheless, we do not think it was the main physiological impact as mosses had a positive response to warming, and increases in their respiration with warming can be similar to or even greater than that observed in lichens (Weber et al ., ; Ouyang & Hu, ).…”
Section: Discussionmentioning
confidence: 99%
“…S3, 4-5 January). This is likely explained by dew formation, a non-rainfall water source found playing an important role in biocrusts Ouyang and Hu, 2017) and also observed at Boodjamulla during the wet season. There are a number of studies that found dew formation was important in biocrust systems, for example the study of Jacobs et al (2000), where in a desert environment in Israel daily amounts of dew ranged between 0.1 and 0.3 mm night −1 .…”
Section: Active Times and Water Relationmentioning
confidence: 99%
“…Biocrust constituents are severely affected by warming; the physiological performance of biocrust-forming lichens and mosses have been found to decrease with warming in experiments conducted in Spain, USA, China and South Africa (Grote, Belnap, Housman, & Sparks, 2010;Maestre, Delgado-Baquerizo, Jeffries, Eldridge, & Ochoa, 2015;Maestre et al, 2013;Maphangwa, Musil, Raitt, & Zedda, 2012;Ouyang & Hu, 2017). These responses have been linked to warming-induced reductions in soil moisture and dew events (Ladrón de Guevara et al, 2014;Ouyang & Hu, 2017).…”
Section: Introductionmentioning
confidence: 99%